Debt management by young couples from Santiago, Chile: From family networks towards the financial system - Lorena Pérez-Roa (economic sociology_the european electronic newsletter, 2018)
On the morning of February 13, 2017, Cristián, a 28-year-old civil engineering graduate of the Universidad de Chile, tried to rob a bank. He was wearing a pajama top, shorts, and sneakers. He had a kitchen knife in his hand and shouted “I want 25 million!” (about USD 50,000). The police caught him as he was trying to escape. One month later, the young man was interviewed by the press while in custody at Jail Number One in Santiago. According to his account, he was desperately trying to solve his economic problems. He owed 25 million pesos to various banks and department stores. He had a mortgage, student loans, and some consumer credit he had obtained in order to help some friends, who had not paid him back. His creditors were relentlessly pursuing him by phone, daily. He was not sleeping because he was constantly wracking his brains about what to do. He didn't seek help from his parents or in-laws due to the embarrassment he felt. Indeed, he never told anyone the full extent of his situation. The previous week he had played the Loto and the Kino (Chilean lottery games of chance), and on the morning of his failed robbery he realized that he had not won. His head “short circuited” and without a thought, he went to the kitchen, grabbed a knife, and went out to rob a bank...
Keywords: 330